Mafhūm al-Basāṭah inda Abdul Malik Karim Amrullah (HAMKA) - Rif’at Husnul Ma’afi; Fadel Kemal Pasha (University of Darussalam Gontor, Indonesia, 2021)
In modern life, humans in groups become two. First, the despicable human being due to exaggeration and Second, a despicable human being is caused to be too lacking. The two groups of humans could not put things in their place and were far from simplicity. To answer a problem above, researchers will examine the thinking of Abdul Malik Karim Amrullah or Hamka an important view in the study of contemporary Muslim scholars. This research wants to explain the concept of simplicity according to Abdul Malik Karim Amrullah and its importance to modern life. This research is a literature study (Library Research). Furthermore, researchers use descriptive methods and analytical methods. And also elaborate and analyze some of his thoughts with the Sufistical Approach. The researchers concluded that the simple concepts carried by Abdul Malik Karim Amrullah (Hamka) are